Common Fixed Point of (ψ, β, L)-Generalized Contractive Mapping in Partially Ordered b-Metric Spaces - Jiang, Binghua; Huang, Huaping; Radenović, Stojan (Axioms, 2023)
The purpose of this paper is to attain the existence of coincidences and common fixed points in four mappings satisfying (ψ,β,L)-generalized contractive conditions in the framework of partially ordered b-metric spaces. The main results presented in this paper generalize some recent results in the existing literature. Furthermore, a nontrivial example is presented to support the obtained results.